Organização do cuidado às pessoas portadoras de diabetes mellitus na perspectiva dos profissionais da atenção primária à saúde - Araujo, Lucieuda Rodrigues de (2020)
Introduction: Diabetes Mellitus is presenting epidemiological importance due to the increasing number of its prevalence, reflecting a dizzying epidemiological and nutritional demographic transition. It becomes a major public health problem, especially for serious complications that the disease causes impairment to the quality of life of people. Adopted as a strategic model for Primary Health Care (PHC), the Family Health Strategy faces a major challenge in facing this disease, which, due to its complex level of approach, requires reflection on the practices of care and the way the model is organizing its capacity to adaptations that involve education, prevention and treatment actions, as well as a good level of professional preparation and service organization for a desirable care. Objective: Analyze the organization of care for people with Diabetes Mellitus (DM) in the perception of professionals in the Family Health Strategy (FHS) and the Extended Family Health Center - Primary Care (EFHC - PC). This is a case study with a qualitative approach. The study scenario was the municipality of Barra de Santana, Paraíba. The study included workers from the FHS teams and EFCH. The Focus Group was the method chosen for data collection. The interview scripts were prepared based on the theoretical framework of the protocol instituted by the Ministry of Health. To assist in the organization and categorization, the technological resource of the Atlas Ti software was used and submitted to Content Analysis. Results: The data were analyzed from five thematic categories: Knowledge and accompanying measures for people with Diabetes Mellitus in the area covered by PHC teams; Management of professionals to people with Diabetes Mellitus challenges and perspectives of the PHC teams; Prevention and management of acute and chronic complications of DM by PHC teams and specific recommendations for people with Diabetes Mellitus and the educational approach to people with Diabetes Mellitus. There was little domain knowledge of the health profile of people with DM weakening the action planning since the early diagnosis, treatment and management suitable for chronic complications, with gaps in the technical field of professionals, lack of supplies and laboratory support, difficulties access to the reference system and the scope of guided educational approach in the traditional model distanced empowerment for supported self-care. Conclusion: The attention given to people with DM in PHC is fragmented, focused on the biologicist model, organized in a spontaneous and unresolved demand. Based on the results of this study suggests that the managers deploy the model of care for chronic conditions and establish a process of permanent education in diabetes, for professionals to prepare as qualify attention.